Blue diamonds the exploits of 14 Squadron RAF 1945-2015 - Napier, Michael (Pen & Sword Aviation, 2015)
Continuing from where he left off in his last publication Winged Crusaders - 14 Squadron RFC and RAF 1915-1945, Michael Napier relays the history of 14 Squadron over the course of the last seventy years, bringing us fully up to date.